Mapping molecular networks within Clitoria ternatea Linn. against LPS-induced neuroinflammation in microglial cells, with molecular docking and in vivo toxicity assessment in zebrafish - Mat Zian, Nurul Farah Adni; Swain, Puspanjali; Mohd Faudzi, Siti Munirah; Zakaria, Norzalina; Wan Ibrahim, Wan Norhamidah; Abu Bakar, Noraini; Shaari, Khozirah; Stanslas, Johnson; Choi, Tae-Ik; Kim, Cheol-Hee (Multidisciplinary Digital Publishing Institute, 2022)
Clitoria ternatea Linn. (CT), or butterfly pea, is an Ayurvedic plant traditionally used as a brain tonic. Recently, it was reported to be of use in treating central nervous system (CNS) disorders, i.e., as an antistress treatment and antidepressant. In the present study, we report a detailed phytochemical profile of the ethyl acetate fraction of the flower of CT (CTF_EA) with significant neuroprotective and anti-neuroinflammatory properties in both LPS-activated BV-2 and SK-N-SH cells. Concurrently, the molecular network (MN) derived from the CTF_EA metabolome allows putative identification of flavonol 3-O-glycosides, hydrocinnamic acids, and primary metabolites. Molecular docking studies suggest that CTF_EA preferentially targets iNOS, resulting in a decrease in nitric oxide (NO). Furthermore, no toxic effects on normal embryonic development, blood vessel formation, and apoptosis are observed when CTF_EA is tested for in vivo toxicity in zebrafish models. The overall preliminary results suggest the anti-neuroinflammatory and neuroprotective effects of CT and provide scientific support for the efficacy of this medicinal plant at local and traditional levels. However, studies on the targeted isolation of bioactive metabolites, in-depth pharmacological efficacy, and safety in mammalian models are urgently needed to expand our understanding of this plant before it is developed into a promising therapeutic agent for brain-related diseases.